Interactivity, engagement, and technology dependence: understanding users' technology utilisation behaviour. Issue 2 (1st February 2017) - Fan, Liu; Liu, Xinmin; Wang, Bingcheng; Wang, Li
ABSTRACT: To better understand users' technology utilisation behaviour, a construct named technology dependence is suggested; as well a technology dependence model is proposed and empirically tested. Based on the literature on marketing, information systems' utilisation, and psychology, a comprehensive set of constructs and hypotheses are compiled with a methodology for testing them in this paper. A questionnaire was designed and data were collected from 255 users of smartphones in Korea, mainly consisting of students and academics. Structural equation modelling was then applied to analyse the data. The result indicated that engagement is the strongest indicator of technology dependence along with user satisfaction. User satisfaction is affected by engagement and responsiveness of the technology. And all three dimensions of interactivity, namely, control, communication, and responsiveness, are revealed to be significant indicators of engagement. Based on the findings, the model develops useful insights into the factors that influence technology dependence and provides new ideas in understanding technology utilisation.